THE EFFECT OF VARIATIONS IN ACTIVATOR CONCENTRATION AND ACTIVATION TIME ON THE QUALITY OF ACTIVATED CARBON BASED ON BANANA STEMS (Prodi Fisika FST UNJA, 2026)
This study aims to synthesize banana stem-based activated carbon through chemical activation using HCl and NaOH at concentrations of 0.5 M and 1 M and activation times of 2 and 4 hours. FT-IR spectra identified –OH, C=O, aromatic C=C, and C–O functional groups in all samples, indicating the potential of banana stems as a raw material for activated carbon, with HCl activation yielding more optimal characteristics. SEM characterization showed that increasing the concentration and activation time resulted in a more porous structure with particle sizes of 0.98–1.63 µm, with the smallest size obtained using 1 M HCl for 4 hours. EDX analysis revealed a dominance of C and O elements, with the highest carbon content of 52.71% (atomic) in 1 M HCl. Moisture content ranged from 1.68–3.13% and met SNI No. 06-3730-1995. Ash content in the HCl treatment was 10%, meeting the standard, while in the NaOH treatment it was 20%. The Pb adsorption test showed the highest efficiency in 1 M HCl at 72.50%, higher than that of NaOH, which decreased to 49.00%.